204k views
1 vote
9(m-3)+3m=7m+43 help me please

2 Answers

3 votes

Answer:

m = 14

Explanation:

9(m - 3) + 3m = 7m + 43 ← distribute parenthesis and simplify left side

9m - 27 + 3m = 7m + 43

12m - 27 = 7m + 43 ( subtract 7m from both sides )

5m - 27 = 43 ( add 27 to both sides )

5m = 70 ( divide both sides by 5 )

m = 14

User Gena
by
4.7k points
4 votes

Answer:

multiply 9 from m and -3

9m - 27 + 3m = 7m + 43

12m - 27 = 7m + 43

12m - 7m = 43+ 27

5m = 70 cut 70 by 5 in 14 times [ 14 x 5= 70 ]

m = 14 answer ❤️❤️ it is 100% correct now!

User Anthony Budd
by
5.4k points